2017
DOI: 10.1139/apnm-2016-0499
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between Helicobacter pylori infection and nonalcoholic fatty liver disease

Abstract: Possible association between Helicobacter pylori infection (HPI) and nonalcoholic fatty liver disease (NAFLD) has been proposed by several studies with inconsistent conclusions. Here, we studied the association between HPI and NAFLD at three levels: 1.) Genetic level; 2.) Small molecular level; and 3.) Clinical level. Relation data between diseases, genes, and small molecules were acquired from Pathway Studio ResNet showed that HPI rate in NAFLD group was significantly higher than that in the non-NAFLD group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 37 publications
1
47
1
Order By: Relevance
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2013 and 2018, three of which were conference abstracts . Our meta‐analysis contained eleven cross‐sectional studies, two case‐control studies, one retrospective cohort study, and one prospective multicenter cohort . Eleven of these studies were from Asia, two studies from the United States, one from Greece, and one from Egypt .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, H pylori ‐I was independently associated with NAFLD, though in other studies their relationship did not remain robust after adjustment for potential cofounders (Table ). It should be underlined that 95 genes were associated with both H pylori ‐I and NAFLD in one study, possibly implying common genetic predisposition. In line, a recent meta‐analysis of six observational studies (one case‐control and five cross‐sectional) also showed higher risk of NAFLD in patients with H pylori ‐I (odds ratios 1.21; 95% confidence interval 1.07‐1.37) …”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 94%
“…Following the aforementioned initial reports, there have been amounting data from observational studies (mostly cross‐sectional) having evaluated the potential association between H pylori ‐I and NAFLD . The main characteristics and results of these studies are summarized in Table .…”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 99%